1996
DOI: 10.1093/molehr/2.10.781
|View full text |Cite
|
Sign up to set email alerts
|

A factor secreted by human embryo stimulates cytokine release by uterine mast cell

Abstract: The existence of a biochemical network of embryo-maternal communication implies that various secreted molecules constitute a signal-response mechanism, important for the process of embryo implantation in mammals. Here we report the purification of a protein with an apparent molecular weight of 136 kDa, responsible for a 2000-fold increase in embryo-derived histamine-releasing factor (EHRF) activity. This protein, purified from medium from the in-vitro culture of 2-8-cell human embryos, by means of affinity chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…Our results and those obtained by others, suggest that there is an interaction between uterine SMC and MC. In addition, it has been shown that the number of MC in the rodent uterus decreases around the time of implantation (Hore and Mehrotra, 1988) and that a factor secreted by the human embryo stimulates cytokine release of 144 endometorial MC in the uterus (Cocchiara et al, 1996). These findings suggest that there is a physiologically relevant interaction between MC and the adjacent endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Our results and those obtained by others, suggest that there is an interaction between uterine SMC and MC. In addition, it has been shown that the number of MC in the rodent uterus decreases around the time of implantation (Hore and Mehrotra, 1988) and that a factor secreted by the human embryo stimulates cytokine release of 144 endometorial MC in the uterus (Cocchiara et al, 1996). These findings suggest that there is a physiologically relevant interaction between MC and the adjacent endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, the high expression in uterus at blastocyst implanting time of early embryo protective molecules (LIF, heme oxygenase, IL‐10, TGF‐β, etc. ), tolerogenic CD4 + CD25 + Foxp3 + T Reg cells (Michimata et al, 2002; Zenclussen, 2006; Zenclussen et al, 2006) and mast cells (Massey et al, 1991; Cocchiara et al, 1996; Dey et al, 2004), together with the recent finding in long‐term allograft tolerance systems of a novel T Reg ‐IL‐9‐mast cell relationship [T Reg (TGF‐β) → IL‐9 → mast cell → (TGF‐β)], endowed with marked immunosuppressive features (Gordon and Galli, 1994; Lu et al, 2006; Zenclussen, 2006; Zenclussen et al, 2006), can probably make more reasonable the hypothesis of SV‐IV involvement in the creation at fetal‐maternal interface of an appropriate tolerant microenvironment characterized by high levels of protective molecules and high density of tolerogenic cells (acquired local immune privilege). In fact, recent data showing that SV‐IV has the in vitro ability to activate human mast cell degranulation with release of histamine (a well known inflammatory agent possessing also antiapoptotic and immunosuppressive properties) and TGF‐β (Hansson et al, 1999; Mellqvist et al, 2000; MacGlashan, 2003; Reynolds et al, 1997; Metafora et al, manuscript in preparation), suggests the possibility of a more active T Reg ‐IL9‐mast cells interaction, with consequent further support to the putative role of SV‐IV in the protection of implanting embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other data demonstrate that human embryos at the preimplantation stage synthesize and secrete a protein, named embryo-derived histamine-releasing factor (EHRF), capable of inducing the release of histamine from basophils and preimplantation uterine-derived mast cells [39,58,59,60]. On the basis of these findings and by considering the immunosuppressive activity of histamine, the authors proposed a novel implantation model.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these findings and by considering the immunosuppressive activity of histamine, the authors proposed a novel implantation model. This model suggests that the local secretion of histamine in vivo by uterine FcεRI+ cells, alone or in cooperation with other factors and/or mechanisms, could play a crucial role in preventing maternal immunorejection of the embryo allograft at the implantation stage [39,58,59,60]. The immunosuppressive features of SV-IV could significantly contribute to this model.…”
Section: Discussionmentioning
confidence: 99%